2019
DOI: 10.1186/s11689-019-9296-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of expressive language development and the left inferior longitudinal fasciculus on listening and reading comprehension

Abstract: BackgroundDuring the first 3-years of life, as the brain undergoes dramatic growth, children begin to develop speech and language. Hallmarks of this progression are seen when children reach developmental milestones, forming the foundation of language. Expressive language milestones, such as the production of a child’s first word, are delayed in 5–8% of children. While for some children delays in reaching these milestones are harbingers of developmental disorders, for others expressive language delays appear to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 122 publications
0
19
0
Order By: Relevance
“…Pearson correlations were performed between the neuropsychological data and DTI parameters for specific tracts according to a priori hypothesis for each test, reducing the need to correct for multiple comparisons. For language, we investigated the correlation between phonological fluency and FA from ILF (Del Tufo, Earle, & Cutting, 2019); for the Trail Making Test, we investigated the association between the scores and the FA of right ILF, as previously investigated in healthy-aging individuals (Perry et al, 2009). However, we were aware of some dissociations of DTI parameters and cognitive impairment (for example, alterations of mean diffusivity without abnormality of FA (Goldstein et al, 2009)) and therefore explored the correlations between DTI indices (all four measurements) of both parahippocampal cingulae (right and left sides) and episodic memory.…”
Section: Methodsmentioning
confidence: 99%
“…Pearson correlations were performed between the neuropsychological data and DTI parameters for specific tracts according to a priori hypothesis for each test, reducing the need to correct for multiple comparisons. For language, we investigated the correlation between phonological fluency and FA from ILF (Del Tufo, Earle, & Cutting, 2019); for the Trail Making Test, we investigated the association between the scores and the FA of right ILF, as previously investigated in healthy-aging individuals (Perry et al, 2009). However, we were aware of some dissociations of DTI parameters and cognitive impairment (for example, alterations of mean diffusivity without abnormality of FA (Goldstein et al, 2009)) and therefore explored the correlations between DTI indices (all four measurements) of both parahippocampal cingulae (right and left sides) and episodic memory.…”
Section: Methodsmentioning
confidence: 99%
“…The ILF connects the occipital and posterior occipito-temporal lobes with the temporal lobe, and it contributes to visual recognition and reading, while subserving the ventral semantic stream connecting the IFOF and SLF (Herbet et al 2018, Herbet et al 2019. Previous reports also mentioned the ILF associate with language networks, and the disruption of the ILF induced dyslexia (Herbert et al 2018, Del Tufo et al 2019). The electric cortical stimulation of the basal temporal language area induced kanji dyslexia, and the speci c area connects with a ventral stream via the ILF, which would contribute to the subcortical network of the kanji-reading process (Enatsu et al 2017).…”
Section: The Subcortical Region Subserving Reading Processmentioning
confidence: 99%
“…For example, for children who have communication problems, more than 65% can be improved when intervention happens before 3 years of age [ 51 ]. Del Tufo et al [ 52 ] reported that early intervention decreased risk of poorer comprehension by almost 40%. In addition, they reported a positive association between receiving early intervention and expressive language development [ 52 ].…”
Section: Early Intervention: Neuronal Plasticity and Resiliencementioning
confidence: 99%
“…Del Tufo et al [ 52 ] reported that early intervention decreased risk of poorer comprehension by almost 40%. In addition, they reported a positive association between receiving early intervention and expressive language development [ 52 ].…”
Section: Early Intervention: Neuronal Plasticity and Resiliencementioning
confidence: 99%